Mining integarl evaluation of the quality of the deposit limestone, Sector Codazzi-La Jagua de Ibírico, Cesar (2008)
The Cesar-Guajira Chapter of the Colombian Society of Geology and the Government of the Cesar in Cooperation with MINERCOL and the Zuliano Institute of the Techonogical Research (INZIT), Venezuela, have done an study on basic geological exploration whih the purpose of knowing the quality, potencial and distribution of the limestone resources within an area of 240 Km2 which is located at the Northeast of the Cesar Departament (State) on the foothill of the Perijá mountain range and that involves the small towns of Codazzi, Becerril and La Jagua de Ibirico. The study results came up whit the definition that the resource presents good quality conditions for cement manufacture, ornamental material and other products, besides important reservations with a total of 4.336'961.900  tons of limestone product, this is what it can be deduce that is does exist the possibility of building a cement plant for the region.